2015
DOI: 10.1088/1674-1056/24/11/110305
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement dynamics of a three-qubit system with different interatomic distances

Abstract: We investigate the tripartite entanglement dynamics of three two-level atoms in a multi-mode vacuum field. By considering the influences of the interatomic distance and the initial condition on the lower bound of concurrence and the tripartite negativity, we show that an optimal interatomic distance can be found to minimize the collective damping. Interestingly, at the same optimal distance, the tripartite entanglement would be maximized in the open dynamics process. In the case of shorter interatomic distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[7] It should be addressed that other relevant contributions have been made in tripartite entangled systems. [8][9][10][11][12][13][14][15][16][17][18] Rindler coordinates are used to describe the viewpoint of uniformly accelerated observers. There are two different sets of coordinates necessary to map field states in Minkowski space-time to Rindler coordinates, which define two disconnected regions in Rindler space-time.…”
Section: Introductionmentioning
confidence: 99%
“…[7] It should be addressed that other relevant contributions have been made in tripartite entangled systems. [8][9][10][11][12][13][14][15][16][17][18] Rindler coordinates are used to describe the viewpoint of uniformly accelerated observers. There are two different sets of coordinates necessary to map field states in Minkowski space-time to Rindler coordinates, which define two disconnected regions in Rindler space-time.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, until the present, the quantification and characterization of the exact amount of entanglement between the different constituent parts of a multi-partite entangled quantum system remains a challenging task and has been calculated only for particular model of decoherence and particular quantum states [39]. Nevertheless, many different entanglement measures for multi-partite entangled quantum systems defined as the sum of the bipartite entanglement measures over all the possible bi-partitions of total quantum system have been proposed during the years [40,41] (see also the review papers [42,43] and the references therein) and some interesting results based on this strategy have been obtained [44][45][46][47][48][49][50][51][52][53][54][55]. For instance, it has been found that for multi-qubit systems, the degree of entanglement robustness tends to increases or decreases with the increase of the number of qubits of the system [8,56].…”
Section: Introductionmentioning
confidence: 99%
“…Now, it is known that the functionality of a natural multichromophoric complex depends mainly on the strength and structure of interactions among electronic states and is dramatically affected by the vibrational degrees of freedom associated either to the complex itself or to its environment. [8][9][10][11][12] By interacting with the electronic states, the phonon environment influences electronic excitation dynamics in various ways depending on the vibrational frequency and the coupling strength. [5] Firstly, phonon modes arising from the low-energy protein vibrations and the solvent have a continuous distribution of frequencies that are below or comparable to the thermal energy scale, k B T , and couple to the electronic states weakly comparing with the coupling strength among electronic states.…”
Section: Introductionmentioning
confidence: 99%